Measuring the Effects of Public Support Schemes on Firms' Innovation Activities. Survey Evidence from Austria - Rahel Falk (Austrian Institute of Economic Research (WIFO), 2006)
This paper discusses conceptual frameworks for measuring the effects of innovation policy and begins with applying conventional descriptive methods to explore how firms rate and rank the merits of public intervention. Based on survey data from some 1200 Austrian firms we then challenge the hypothetical survey question ("What would you have done if public support was denied?") by comparing the respective answers with changes that actually occurred when public assistance was refused. This is a contribution to the ongoing literature as is the attempt to relate any of the observed additionalities to the firms' characteristics, their perceived barriers to innovation and the degree they make use of the public support system. The effects of policy interventions prove to be cumulative in a dual sense. On the one hand, our results confirm the well-known notion that large firms make the best use of funds. On the other hand, substantial changes in the way a company undertakes R&D&I-related activities appear to only result from multiple policy interventions of different kinds. While supported firms tend to immediately increase their resources devoted to innovation projects, the result-based concepts of additionality only come into effect once a threshold level of intervention has been reached. Acknowledging that a public innovation support system already incentivises potential beneficiaries to change their innovation-related behaviour, and that eventual success in terms of outcomes does not arise from some discrete support measure, but from the synergies of multiple policy action, we conclude that future work should focus more on the evaluation of portfolios of programmes and their interactions.
Keywords: 330; innovation policy; policy evaluation; methods; Innovation; Technologiepolitik; Wirkungsanalyse; Unternehmen; Österreich; Meinung